Genotyping of Salmonella with lineage-specific genes: correlation with serotyping. (August 2016) - Zou, Qing-Hua; Li, Ren-Qing; Liu, Gui-Rong; Liu, Shu-Lin
Highlights: Seven newly selected genes that have a good power to discriminate different Salmonella serovars were identified. The tree based on the concatenated sequence of the seven newly selected genes showed a more reasonable phylogenetic relationship than the concatenated MLST genes tree and the rpoB gene tree. Some specific genes that can be used to differentiate Salmonella lineages were found. Summary: Background: The bacterial genus Salmonella encompasses a large number of serotypes that are genetically very similar but biologically quite different, especially in pathogenic properties and host specificity. Serotyping has been used for the classification, identification, and epidemiological investigation due to its excellent discriminating power, but it cannot distinguish the different pathogenic lineages within a polyphyletic serotype. Additionally, very few institutions have the comprehensive set of antisera for typing. Therefore various studies have been performed to explore alternative assays to differentiate Salmonella isolates, such as the search for genes that can be used as potential molecular substitutes for serotyping. However, the genes tested so far have often given inconsistent results. Methods: In this study, the discriminating power of seven genes to differentiate 309 Salmonella strains representing 26 serotypes was evaluated and the results were compared with those of other methods. Results: The seven newly selected genes have a good power to differentiate different serovars. The tree based on the concatenated sequences of these genes revealed phylogenetic relationships of the bacteria consistent with that of the whole genome tree. Conclusion: Individual Salmonella lineages each have specific genes that can be used to differentiate Salmonella isolates on a phylogenetic basis.